2007
DOI: 10.1016/j.jfi.2007.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Herd behavior in the Japanese loan market: Evidence from bank panel data

Abstract: This paper investigates whether Japanese banks had been following herd behavior in the domestic loan market from 1975 through 2002. Applying the technique developed by Lakonishok, Shleifer, and Vishny (LSV) (1992, J. of Fin. Econ.) to the data of loans outstanding to different types of borrowers, we obtain evidence indicative of the existence of herding. Consistent herding during the entire sample period is observed among regional banks, whereas city banks had been following a cyclical herd behavior with one p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
43
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 44 publications
9
43
0
Order By: Relevance
“…The results indicate that syndication in the later rounds of financing, rather than in the first round of financing, has a more negative impact on the IPO value; thus suggesting that as Lerner emphasized, the effects of syndication differ between the first and later rounds of financing. Several studies have found imitative and herd behavior for Japanese firms and banks (e.g., Lieberman and Asaba, 2006;Uchida and Nakagawa, 2007). In the later rounds of financing for pre-IPO firms, VC firms have more incentive to participate in investments to better their reputations.…”
Section: As Shown Inmentioning
confidence: 99%
“…The results indicate that syndication in the later rounds of financing, rather than in the first round of financing, has a more negative impact on the IPO value; thus suggesting that as Lerner emphasized, the effects of syndication differ between the first and later rounds of financing. Several studies have found imitative and herd behavior for Japanese firms and banks (e.g., Lieberman and Asaba, 2006;Uchida and Nakagawa, 2007). In the later rounds of financing for pre-IPO firms, VC firms have more incentive to participate in investments to better their reputations.…”
Section: As Shown Inmentioning
confidence: 99%
“…Buch and Lipponer (2006) show that foreign direct investments of German banks tend to concentrate in OECD countries. Uchida and Nakagawa (2007), Nakagawa (2008), and Nakagawa and Uchida (2010) provide the strong evidence of herding by Japanese banks in the period of the asset price bubble in the late 1980s. 2 In spite of many studies examining the existence of herding by banks, few studies have examined how bank herding affects the real economy.…”
Section: Introductionmentioning
confidence: 94%
“…Commercial banks probably are not using the same standards or preferences to evaluate the various loans for various industries. According to the study result of the Japanese banks, Uchida and Nakagawa (2007) has proved that banks observe each other's for different operation methods in order to reduce the management risk. The situation causes the loans from different banks to some specific industries have existed obvious differentiation when comparing whole partials.…”
Section: Industrial Environmental Factorsmentioning
confidence: 99%